2015
DOI: 10.1016/j.watres.2015.08.047
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pH on fluorescent dissolved organic matter photo-degradation

Abstract: A novel semi-continuous excitation emission matrix (EEM) fluorescence and absorbance monitoring system has been developed. Full EEMs were collected simultaneously with absorbance spectra every 20 min during 24 h solar-simulated irradiation experiments, and the kinetic change of fluorescence of Suwannee River natural organic matter IHSS standard material (SRNOM) at various pH values was investigated. Parallel factor analysis (PARAFAC) was then used to isolate the photo-labile and pH-influenced fluorescent compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 61 publications
7
56
1
Order By: Relevance
“…As C5 was not enriched in STSW, we suggest that C5 undergoes further photo-degradation processes near the surface. This is in agreement with those studies, where components, similar to C5, in terms of spectral properties, were reported to be subject to photo-degradation [Stedmon and Markager, 2005;Stedmon et al, 2007;Ishii and Boyer, 2012;Timko et al, 2015].…”
Section: 1002/2016jc011906supporting
confidence: 94%
See 1 more Smart Citation
“…As C5 was not enriched in STSW, we suggest that C5 undergoes further photo-degradation processes near the surface. This is in agreement with those studies, where components, similar to C5, in terms of spectral properties, were reported to be subject to photo-degradation [Stedmon and Markager, 2005;Stedmon et al, 2007;Ishii and Boyer, 2012;Timko et al, 2015].…”
Section: 1002/2016jc011906supporting
confidence: 94%
“…In the following stages of the incubations, the component was shown to be degraded. Timko et al [2015] also reported of a C5-similar component, which was highly susceptible to light. As C2 and C5 occurred independently near the surface ( Figure 6), and because the 5-component PARAFAC model was stable only for the upper water column, we speculate that formation and removal of C5 in the water column is induced by sunlight.…”
Section: Characteristics Of Dommentioning
confidence: 95%
“…Reproducible photodegradation experiments1041 undertaken on the deep-sea SPE-DOM (Sargasso Sea 4,530 m), SRNOM and three different strains of Synechococcus SPE-DOM (Supplementary Fig. 8) showed that the photodegradation of the Synechococcus SPE-DOM samples behaved in a similar manner to the deep-sea SPE-DOM, whereas the maximum fluorescence loss of SRNOM occurred at longer emission wavelengths.…”
Section: Resultsmentioning
confidence: 94%
“…A custom-built irradiation system with a solar simulator was used to irradiate samples41. A volume of 1 ml of the previously dried (removal of methanol) SPE-DOM was re-dissolved in pure water and added to an equilibrator vial containing a stir bar to ensure proper aeration and prevent oxygen starvation during irradiation.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, reduced soil acidity leads to a decrease in the adsorption capacity of the soil, increased DOM solubility, and higher export of terrestrial DOM (Jardine, McCarthy, & Weber, 1989). The mobilized DOM has high molecular weight and a high sensitivity to ultraviolet (UV) light and photoreactive damage (Lu, Yuan, Tao, & Tang, 2015;SanClements et al, 2012;Timko, Gonsior, & Cooper, 2015). Due to these properties, the mobilized DOM may be less available to bacterial uptake ( Figure 2) (Ekstr€ om et al, 2016).…”
Section: Introductionmentioning
confidence: 99%